Reasons for delays in treatment of patients suffering from malignant cancers in Podkarpackie voivodeship - Podgórska, Justyna; Kruk, Wacław; Cichocka , Izabela (Polish Journal of Public Health, 2013)
Introduction.  In  the  case  of  oncological  patients,  early implementation of treatment is a  key matter. Any delays oc- curring on each of the levels of diagnostic and therapeutic processes  may affect the outliving of the patients. Elimina- tion of their reasons could reduce the time  scale of the de- lays,  increase  the  percentage  of  cancer  instances  detected in initial stages, as well as improve patients’ prognoses.Aim. The basic objective of this thesis was to identify the main reasons for the delays in the  treatment of oncological patients.  The  additional  goal  was  to  establish  the  sources of information on prophylaxis collected by the patients.Material and methods. The research comprised108 peo- ple who were treated in a stationary treatment system in two specialized  oncology  centers  in  Podkarpacie.  The  method consisted in a diagnostic poll and the employed technique was a survey carried out in the form of a standardized  inter- view.Results. Among the reasons for the delays that patients contributed  to  the  most  commonly  mentioned  were:  lack of knowledge about the symptoms that could suggest cancer and as well as disregarding the symptoms. Eighty-one per cent of the respondents gave more than one reason. Among all respondents, 84% do not know the symptoms that may suggest cancer, 98% claim that actions, which promote this area of knowledge, are needed, and the highest rated source of information is a GP.Conclusions. The majority of the reasons for the delays in cancer treatment are those, which lie on the side of pa- tients and these are also responsible for the longest average time of procrastination. Delays in treatment on account of the health care system organization seem to be a relatively smaller problem in comparison to those on the side of pa- tients.  General  practitioner,  who  constitutes  an  essential link in the system of fight against cancer in the population, is considered by the patients to be the most reliable source of information on oncological prophylaxis.